MENINGKATKAN KONSEP BILANGAN MELALUI BERMAIN KENCLENG KELERENG - Sri Sugiarti; Ema Aprianti (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
The purpose of this study was to determine the effectiveness the method of playing kencleng marbles in improving the recognize the concept of numbers in early childhood. The research method used is a quasi-experimental method that is using two classes. Data analysis was performed using descriptive for qualitative data, and using statistics for quantitative data. Based the results of data analysis, the average at the class experimental pretest was 50 and the class control 47.5. The applicat of the marbling kencleng playing method was implemented well. This is evident from the average posttest score of the class experiment which increased by 31.6 to 81.6. While the average control class is 53.3. This research data has a significance value of 2-tailed 0.02, which means 0.05, then the data has a significan different in the ability to recognize the concept of numbers between the class experimental who were given the method of playing marbles and the control class given conventional methods. Normalized gain test calculation shows this N-Gain Score for the experimental class of 64.9% is included in the quite effective category. While the class control Score N-Gain of 29.5% is included in the ineffective category. Thus, the application of the method of playing kencleng marbles has been completed in accordance expected goals of increasing the ability to recognize the concept of numbers in group A TK Bhayangkari 49.Penelitian ini dilakukan guna mengetahui efektifitas metode bermain kencleng kelereng dalam meningkatkan kemampuan anak usia rendah terhadap kemampuan mengenal konsep bilangan. Pada  penelitian ini merode yang digunakannya adalah metode quasi eksperimen yaitu menggunakan dua kelas. Berdasarkan analisis data didapatkan rata-rata pretest kelompok eksperimen sebesar 50 dan kelompok kontrol sebesar 47,5. Adapun penerapan metode bermain kencleng kelereng  telah  terlaksana dengan baik. Hal demikian terlihat dari rata-rata nilai posttest kelompok eksperimen meningkat sebesar 31,6 sehingga menjadi 81,6. Sedangkan rata-rata kelompok kontrol sebesar 53,3. Data penelitian ini memiliki nilai signifikasi 2-tailed  0,02 yang artinya kurang dari 0.05, maka data tersebut memiliki perbedaan yang sangat signifikan pada kemampuan mengenal konsep bilangan antara kelompok eksperimen yang diberi metode bermain kencleng kelereng dan kelompok kontrol yang diberi metode konvensional. Perhitungan uji gain normalisasi menunjukkan bahwa N-Gain Score untuk kelompok eksperimen sebesar 64.9% termasuk dalam kategori cukup efektif.  Sementara N-Gain Score kelas control sebesar 29.5% termasuk dalam kategori tidak efektif. Dengan demikian, penggunaan metode bermain kencleng kelereng telah selesai sesuai dengan tujuan yang diharapkan yakni dapat meningkatkan konsep bilangan pada kelompok A TK Bhayangkari 49.